BEBERAPA PERSPEKTIF TEORI PENYUSUNAN BAHAN AJAR KETERAMPILAN BERBAHASA INDONESIA - Pratiwi, Yuni (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2010)
Facing continuous global changes, the Indonesian government views that acentralized curriculum is incapable of accommodating the development of knowledge andcommunity needs in the local, national, and global levels. A competence-based curriculumis constructed with an expectation that in the national education system graduates havecompetitive and comparative advantages. The Indonesian Language subject equipsstudents with awareness that the language is the national identity that unifies Indonesianpeople as a nation and simultaneously the subject develops their linguistic andcommunicative competence. Teachers' understanding of the scope of the competencecontents and theoretical perspectives in instructional materials development affects thelevel of the competence attainment. Theoretical perspectives help teachers to developinstructional materials for language skills relevant to students' communicative needs inreal life.Keywords: perspective, instructional materials for the Indonesian language skills,School-Based Curriculum